Corporate Sustainability Due Diligence as a Transformative Element of EU Corporate Law - Primec, Andreja; Pastirk, Gal (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
The regulation of corporate conduct with respect to environmental and human rights impacts has assumed increasing prominence in EU company law, reflecting developments in corporate sustainability law. This article examines the development of corporate sustainability law in the EU, focusing on corporate sustainability due diligence as a component of EU corporate law and an emerging framework shaping corporate responsibilities. It analyses the Omnibus I reform of the Corporate Sustainability Due Diligence Directive (CSDDD) and evaluates its implications for company law and corporate governance. The article explores the simplifications introduced by the reform, particularly regarding the scope and structure of due diligence as a risk-based, continuous system for identifying, preventing, mitigating and accounting for adverse impacts. It argues that, notwithstanding these adjustments, due diligence remains a legal standard of corporate governance. At the same time, the reform narrows the circle of obligated companies and underscores the need for coherent implementation.